Bioremediation membrane and preparation method thereof

By constructing a biorepair membrane of the gel layer and umbilical cord layer crosslinked by hydroxyapatite, chitosan and sodium alginate, the problems of weak repair membrane materials and insufficient mechanical properties in the prior art are solved, and efficient tissue repair and regeneration are achieved.

CN117018292BActive Publication Date: 2025-03-04MOBILE MEDICAL TECH (SHANGHAI) CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310788147.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2025-03-04
Estimated Expiration
2043-06-29

AI Technical Summary

Technical Problem

The existing biorepair membrane materials are thin and prone to tear, and have insufficient bone conductivity and mechanical properties, so they are not suitable for the repair of oral defects and bone defects alone.

Method used

A biorepair membrane consisting of a gel layer formed by cross-linking of hydroxyapatite, chitosan and sodium alginate and an umbilical cord layer made of umbilical cord tissue is used. The film is pressed and lyophilized by a mold to form a bilateral structure of biorepair film, which enhances the adhesion and fit of the film.

Benefits of technology

It improves the bioactivity, biodegradability, tissue fit, bone conductivity and mechanical properties of the biorepair membrane, promotes cell proliferation and differentiation, and realizes rapid vascularization and repair and regeneration of defect areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117018292B_ABST
    Figure CN117018292B_ABST
Patent Text Reader

Abstract

The present invention provides a biorepair membrane and a preparation method thereof, comprising a gel layer and an umbilical cord layer; the gel layer is cross-linked by hydroxyapatite, chitosan and sodium alginate; the umbilical cord layer is adhered to one side of the gel layer, and the umbilical cord layer is a sheet structure composed of umbilical cord tissue, and the umbilical cord tissue is formed from an umbilical cord from which vascular cells are mechanically removed. The biorepair membrane of the present invention contains natural active ingredients that can promote and induce cell proliferation and differentiation, achieve rapid vascularization and repair and regeneration of defective areas, and has good biological activity, biodegradability, tissue adhesion, bone conductivity and mechanical properties, good biocompatibility, no cytotoxicity, and no immunogenicity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedical materials, and in particular to a biorepair membrane and a preparation method thereof. Background Art

[0002] Biorepair membranes used in dental clinical treatments utilize the membrane's barrier function to isolate the lesion from the surrounding tissue, creating a relatively closed tissue environment and inducing osteoblast aggregation and differentiation, ultimately achieving targeted tissue repair. Biorepair membranes can be used in combination with bone repair materials such as bone meal to fill and repair dental and maxillary bone defects or bone loss following oral surgery. They improve implant integration with the surrounding alveolar bone, addressing physiological bone resorption or bone loss caused by periodontal disease or edentulism, and enhancing wound healing. However, the barrier membrane and bone repair material typically need to be implanted sequentially, increasing tissue tension. Furthermore, factors such as membrane displacement caused by bleeding at the tissue defect can lead to poor closure of the barrier membrane at the tissue defect and loss of bone repair material, compromising treatment effectiveness. The periosteum is a strong, double-layered connective tissue covering the bone surface, excluding joints. It consists of a fibrous layer and a germinal layer. The fibrous layer is primarily composed of coarse collagen fiber bundles, which form a network and serve to stabilize the periosteum and ligaments. The germinal layer, located adjacent to the outer surface of the bone, is loosely arranged and has the ability to form bones, hence its name. While the periosteum itself cannot induce new bone formation, it provides a supportive microenvironment that promotes the regeneration of new bone tissue, making it particularly important for the rapid healing of fractures and bone defects.

[0003] Currently, the preferred biodegradable collagen-based biorepair membranes on the market are mostly freeze-dried bioscaffold membranes with varying pore sizes. These membranes function as simple physical barriers, resulting in poor bioactivity and osteogenic properties. Furthermore, most membrane materials are thin and prone to tearing, with limited osteoconductivity and mechanical properties, making them unsuitable as standalone repair materials for oral and bone defects. The development of composite polymer membranes is an important area of ​​research.

[0004] At present, some patents have disclosed the preparation technology of double-layer or multi-layer oral repair membranes. For example, the Chinese patent with publication number CN109513046A discloses an absorbable oral repair membrane and its preparation method, which presses gelatin-polycaprolactone-gelatin to obtain a three-layer oral repair membrane. However, its pressing temperature is 55-65°C, which is relatively high and is only suitable for materials with high temperature tolerance, not for collagen membrane pressing. The Chinese patent with publication number CN104922732 A discloses a method for preparing oral biofilm, in which collagen and chondroitin sulfate are prepared into a slurry, which is pressed into a collagen composite film by vacuum freeze drying, and then the collagen-chondroitin sulfate slurry is sprayed into the two layers of collagen composite film, and vacuum freeze dried again to obtain a collagen-chondroitin sulfate composite oral biofilm. The structure of the oral biofilm in this patent is made by configuring it into a slurry, and the pressed double-layer structure does not provide the membrane material with better mechanical properties, etc., and the bonding force between the membranes is insufficient. Furthermore, oral membranes in the prior art all need to be rehydrated for clinical use, and the membranes prepared by the disclosed methods have the defects of insufficient bonding between layers and easy delamination.

[0005] Therefore, it is necessary to provide a novel bioremediation membrane and a preparation method thereof to solve the above-mentioned problems existing in the prior art. Summary of the Invention

[0006] The purpose of the present invention is to provide a biorepair membrane and a preparation method thereof. By constructing a biorepair membrane composite of umbilical cord and hydroxyapatite, the problems in the existing technology that the repair membrane material is thin and easy to tear, has insufficient bone conductivity and mechanical properties, and is not suitable for repairing oral defects and bone defects alone are solved.

[0007] To achieve the above-mentioned purpose, the biorepair membrane of the present invention includes a gel layer and an umbilical cord layer; the gel layer is formed by cross-linking hydroxyapatite, chitosan and sodium alginate; the umbilical cord layer is adhered to one side of the gel layer, and the umbilical cord layer is a sheet structure composed of umbilical cord tissue, and the umbilical cord tissue is formed from the umbilical cord by mechanically removing vascular cells.

[0008] The beneficial effects of the biorepair membrane of the present invention are: the gel layer is cross-linked by hydroxyapatite, chitosan and sodium alginate, the umbilical cord layer is adhered to one side of the gel layer, the umbilical cord layer is a sheet structure composed of umbilical cord tissue, and the umbilical cord tissue is formed in the umbilical cord by mechanically removing vascular cells, wherein the various natural active ingredients retained by the umbilical cord layer can improve the healing ability of wounds and reduce scars produced after surgery; the hydroxyapatite is similar to the composition and structure of bones, has high strength and toughness, can simultaneously improve the survival rate of osteoblasts and the amount of bone mineralization, and guide bone defect repair, sodium alginate and chitosan are natural polymer materials with a wide source, similar to the extracellular matrix, and can form excellent properties such as interpenetrating or semi-interpenetrating networks in the polymer hydrogel matrix, and the double network structure The gel scaffold with the structure can enhance the mechanical properties of the hydrogel, so that it can maintain its integrity after absorbing liquid and swelling when it is in close contact with the surface of the tissue defect without causing the membrane to deform or shift. That is, the biorepair membrane simultaneously possesses the natural bioactive components of the umbilical cord, the high osteogenic performance and osteoconductivity of hydroxyapatite, and the excellent mechanical properties of sodium alginate and chitosan, so that the natural active components contained in the biorepair membrane can promote and induce cell proliferation and differentiation, achieve rapid vascularization and repair and regeneration of the defect area, and have good bioactivity, biodegradability, tissue adhesion, osteoconductivity and mechanical properties, good biocompatibility, no cytotoxicity, and no immunogenicity; it solves the problems in the existing technology that the repair membrane material is thin and easy to tear, and has insufficient osteoconductivity and mechanical properties, and is not suitable for repairing oral defects and bone defects alone.

[0009] Preferably, the biorepair membrane is used for bone tissue repair and oral soft tissue repair. Its beneficial effects are: a wide range of applications and strong versatility. When the biorepair membrane is placed between oral soft tissue and bone defects, or between bone tissue and bone defects, it can create a relatively closed bone regeneration environment. The biorepair membrane, facing the oral soft tissue or bone tissue, can prevent soft tissue cells with faster migration speeds from entering the bone defect area, thereby making the biorepair membrane serve as an excellent barrier protection. In addition, the hydroxyapatite in the gel layer of the biorepair membrane is conducive to promoting osteogenesis and improving the mechanical properties of the biorepair membrane. The bioactive substances in the umbilical layer of the biorepair membrane can effectively promote soft tissue repair and regeneration, making the biorepair membrane applicable to oral soft tissue repair and bone tissue repair.

[0010] Preferably, when the biorepair membrane is used for oral soft tissue repair, the mass ratio of the chitosan to the sodium alginate is (1:1) to (1:3), and the concentration of the hydroxyapatite in the polymer hydrogel matrix composed of the chitosan and sodium alginate is 0.1% (w / v) to 0.3% (w / v). Its beneficial effects are: sodium alginate and chitosan have good biocompatibility, biodegradability, and antibacterial properties, and hydroxyapatite can ensure the mechanical properties and osteogenic properties of the biorepair membrane; within this ratio range, cross-linking is sufficient, the surface of the gel layer is smoother and the shape is more regular, and the pore size distribution in the biorepair membrane is uniform and the morphology is flat. If the hydroxyapatite content is too high, the freeze-dried biorepair membrane will become brittle and the morphology will not be well maintained.

[0011] Preferably, when the biorepair membrane is used for bone tissue repair, the mass ratio of the chitosan to the sodium alginate is (1:1) to (1:3), and the concentration of the hydroxyapatite in the polymer hydrogel matrix composed of the chitosan and sodium alginate is 0.2% (w / v) to 0.4% (w / v). Its beneficial effects are: sodium alginate and chitosan have good biocompatibility, biodegradability, and antibacterial properties, and hydroxyapatite can ensure the mechanical properties and osteogenic properties of the biorepair membrane; within this ratio range, cross-linking is sufficient, the surface of the gel layer is smoother and the shape is more regular, and the pore size distribution in the biorepair membrane is uniform, with a flat morphology. If the hydroxyapatite content is too high, the freeze-dried biorepair membrane will become brittle and the morphology will not be well maintained. In the case of a large area of ​​bone defect, the mechanical properties of the umbilical cord layer itself cannot provide sufficient support, and it is easily deformed by squeezing of soft tissues such as muscles, making it difficult to achieve a good therapeutic effect. Therefore, when the biorepair membrane is used for bone tissue repair, the concentration of hydroxyapatite is higher, which is beneficial to improving the mechanical properties of the biorepair membrane, so as to better promote bone repair.

[0012] Preferably, the side of the umbilical cord layer facing away from the gel layer is a smooth surface, and the side of the gel layer facing away from the umbilical cord layer is an indentation surface, and the indentation surface is provided with a convex structure and a concave structure. Its beneficial effect is that the double-sided structure can fit well with the part to be repaired, provide a relatively closed tissue growth environment, provide good space and time for bone regeneration, and promote tissue repair and regeneration. Among them, the convex structure and the concave structure of the indentation surface can effectively increase the degree of fit and contact surface area between the biorepair membrane and the part to be repaired, improve the fit between the biorepair membrane and the tissue defect, and improve clinical use and treatment effects. The biorepair membrane has an indentation surface and a smooth surface. The double-sided structure not only fits well with the part to be repaired, can selectively guide cell growth, and can be degraded synchronously with the reconstruction of the new tissue. The method solves the problem in the prior art that there is a gap between the biofilm with smooth surfaces on both sides and the tissue defect, which causes fibroblasts and epithelial cells with faster growth and migration rates to enter the bone defect area, forming competitive inhibition with osteoblasts with slower growth and migration rates, and adversely affecting the healing of bone tissue.

[0013] Preferably, the gel layer and the umbilical cord layer are adhered and fixed by freeze-drying through a mold. The mold comprises a first surface and a second surface disposed opposite each other. The first surface is an indentation surface adapted to the indentation surface and provided with a raised structure and a recessed structure, while the second surface is a smooth surface adapted to the smooth surface. This advantageous effect is that the mold can be used to freeze-dry a biorepair membrane into a membrane with different structures on both sides. Specifically, the indentation surface provided with the raised and recessed structures results in a surface of the freeze-dried biorepair membrane having raised and recessed structures, thereby effectively increasing the biorepair membrane's fit and contact surface area with the repaired site, improving the biorepair membrane's fit with the tissue defect, and enhancing clinical use and therapeutic efficacy. This solves the problem in the prior art where a gap exists between a biorepair membrane with smooth surfaces on both sides and the tissue defect, causing fibroblasts and epithelial cells (with faster migration rates) to enter the bone defect area, competitively inhibiting osteoblasts (with slower migration rates), and adversely affecting bone tissue healing.

[0014] Preferably, the umbilical cord is an allogeneic umbilical cord. Its beneficial effects include: the allogeneic umbilical cord has a porous double-layer structure, with one layer of densely arranged collagen fibers and another layer of loosely arranged collagen fibers; it also contains multiple bioactive ingredients, has low immunogenicity, and has unique biological properties that promote cell attachment and tissue regeneration and healing, which is of great significance in clinical applications.

[0015] Further preferably, the umbilical cord tissue is derived from the human body. Its beneficial effects are: using human umbilical cord tissue as the basal layer breaks the limitation of using animal-derived raw materials to prepare biorepair membranes, which can effectively avoid the patient's rejection reaction; the umbilical cord contains basic fibroblast growth factor, insulin-like growth factor, platelet-derived growth factor and transforming growth factor, etc., which can be used as a sustained-release carrier of growth factors to promote cell proliferation and osteogenic activity; and human umbilical cord has low immunogenicity, and the natural active ingredients are mainly composed of collagen, glycoproteins, mucopolysaccharides and growth factors. It can not only provide cells with a biomimetic three-dimensional support carrier, but also promote the migration, proliferation and differentiation of host cells through the interaction of various proteins and growth factors with the host to promote tissue regeneration and repair.

[0016] Preferably, the umbilical cord layer has a double-layer porous structure, comprising a dense layer and a loose layer, wherein the pore size of the dense layer is smaller than that of the loose layer, the loose layer is adhered and fixed to the gel layer, and the dense layer is provided with the smooth surface. Its beneficial effects are as follows: the biorepair membrane is used to be placed between oral soft tissue or bone tissue and the bone defect to create a relatively closed bone regeneration environment; therefore, the dense layer with a small pore size facing the soft tissue can block the fibroblasts and epithelial cells with a faster migration speed from entering the bone defect area, thereby acting as a barrier; compared to the prior art double-layer membrane structure in which the two different layers are simply fixed by pressing, the loose layer in the present invention is adhered to the gel layer, and through repeated freeze-thaw treatment, the gel layer is adsorbed into the micropores of the loose layer of the umbilical cord layer, thereby enhancing the adhesion between the gel layer and the umbilical cord layer, that is, greatly improving the bonding strength between the bonding interfaces, solving the problem of insufficient bonding strength between the membrane layers and easy delamination in the prior art.

[0017] Preferably, the pore size of the loose layer is 20 μm to 100 μm. Its beneficial effects are as follows: the umbilical cord itself has a natural double-sided structure, and the dense layer retains the natural collagen fiber dense structure of the umbilical cord, which is used to face the soft tissue, effectively preventing fibroblasts and epithelial cells from growing into the bone defect area, supporting soft tissue formation, and preventing soft tissue from growing into the bone defect area; the collagen in the loose layer is relatively sparsely arranged and has a certain pore size, which can achieve close integration with the gel layer in some areas during repeated freezing and thawing. The present invention realizes the preparation of a double-layer membrane that does not delaminate after rehydration, so that when applied to tissue defects, the dense layer and the loose layer can effectively play their respective roles.

[0018] The method for preparing the bioremediation membrane of the present invention comprises the following steps:

[0019] Providing an original umbilical cord, mechanically removing blood vessels in the original umbilical cord to form umbilical cord tissue to be shaped, and trimming the umbilical cord tissue to be shaped into an umbilical cord layer with a sheet-like structure;

[0020] preparing a sodium alginate solution, a chitosan solution, and a hydroxyapatite solution respectively, uniformly mixing the chitosan solution, the sodium alginate solution, and the hydroxyapatite solution to obtain a gel solution, and then subjecting the gel solution to a cross-linking reaction to obtain a gel layer;

[0021] The umbilical cord layer is adhered and fixed to the gel layer to prepare the biorepair membrane.

[0022] The beneficial effects of the preparation method of the biorepair membrane of the present invention are as follows: by providing an original umbilical cord, mechanically removing blood vessels in the original umbilical cord to form umbilical cord tissue to be reshaped, and trimming the umbilical cord tissue to be reshaped into an umbilical cord layer with a sheet structure; respectively preparing a sodium alginate solution, a chitosan solution and a hydroxyapatite solution, mixing the chitosan solution, the sodium alginate solution and the hydroxyapatite solution to obtain a gel solution, and then cross-linking the gel solution to obtain a gel layer; adhering and fixing the umbilical cord layer to the gel layer to obtain the biorepair membrane, wherein the various natural active ingredients retained in the umbilical cord layer can improve the healing ability of wounds and reduce scars produced after surgery; the components of the hydroxyapatite and bone and The structures are similar, with high strength and toughness, and can simultaneously improve the survival rate and bone mineralization of osteoblasts, and guide bone defect repair. Sodium alginate and chitosan are natural polymer materials with a wide source. Similar to the extracellular matrix, they can form interpenetrating or semi-interpenetrating networks in the polymer hydrogel matrix and other excellent properties. The double-network structure of the gel scaffold can enhance the mechanical properties of the hydrogel, so that it can adhere closely to the surface of the tissue defect and still maintain its integrity after absorbing liquid and swelling without causing the membrane to deform and shift, so that the prepared biorepair membrane contains natural active ingredients that can promote and induce cell proliferation and differentiation, achieve rapid vascularization and repair and regeneration of the defect area, and has good biological activity, biodegradability, tissue fit and mechanical properties, good biocompatibility, no cytotoxicity, and no immunogenicity.

[0023] Preferably, the step of uniformly mixing the chitosan solution, the sodium alginate solution and the hydroxyapatite solution to obtain a gel solution comprises: dripping the chitosan solution into the sodium alginate solution at a rate of 1 mL / min to 2 mL / min, and stirring and mixing to obtain a polymer hydrogel matrix; adding the hydroxyapatite solution into the polymer hydrogel matrix at a rate of 1 mL / min to 2 mL / min, and stirring and mixing to obtain the gel solution. The beneficial effect is that the configuration of the gel solution is to first prepare the sodium alginate solution, and then slowly drip the chitosan solution into the sodium alginate solution. This order of addition can avoid the problem of mutual adhesion and poor connectivity of the pores inside the material, thereby obtaining a porous membrane material with suitable pore structure, good elasticity and mechanical properties, and the pore structure is evenly distributed, without adhesion, and there is no problem of uneven size distribution.

[0024] Preferably, the step of cross-linking the gel solution to obtain a gel layer comprises: ultrasonically removing bubbles from the gel solution and then vacuum freeze-drying for 12 to 24 hours to obtain a gel membrane material; soaking the gel membrane material in a calcium chloride solution for cross-linking for 0.1 to 1 hour, then soaking it in a cross-linking agent solution for 1 to 4 hours, and then soaking and washing it with deionized water 1 to 3 times, with each soaking and washing time being 5 to 10 minutes, to obtain the gel layer. Its beneficial effect is that the calcium ions in the calcium chloride solution can complex and cross-link with sodium alginate to form an egg-box structure, and then form a cross-linked network structure through group accumulation, so that the gel solution is converted into a hydrogel, so that the obtained gel layer has optimal stability and adsorption capacity; soaking in the cross-linking agent can further improve the mechanical properties of the gel layer, and soaking and washing it with deionized water 1 to 3 times, with each soaking and washing time being 5 to 10 minutes, to wash away excess cross-linking agent.

[0025] Preferably, the step of adhering and fixing the umbilical cord layer to the gel layer to obtain the biorepair membrane includes: in an environment with a temperature of 11°C to 15°C, covering one side of the dense layer in the umbilical cord layer on the smooth surface of the mold, adhering one side of the gel layer to one side of the loose layer in the umbilical cord layer, and then covering the indentation surface of the other mold on the other side of the gel layer. Its beneficial effects are: the processing environment temperature of the umbilical cord layer is 11°C to 15°C, that is, rapid processing in a low-temperature environment can retain the natural active ingredients of the umbilical cord to the greatest extent; after the mold pressing and freeze-drying treatment, the biorepair membrane has a double-sided structure with an indented surface and a smooth surface, and the loose layer of the sheet umbilical cord layer is bonded to the gel layer, and then through subsequent freeze-thaw cycles, cross-linking with a cross-linking agent and vacuum freeze-drying treatment, the loose layer and the gel layer can be more deeply integrated, without obvious stratification, and the structural continuity is good; the surface of the part to be repaired is usually not flat, and the presence of the indentation structure can effectively increase the degree of fit between the repair membrane and the part to be repaired and the contact surface area, which is beneficial to promoting tissue healing; and the gel layer with hydroxyapatite covers the indentation surface of the mold, even if the gel layer has an indentation surface, so that the indentation surface of the gel layer with hydroxyapatite faces the bone defect, which can simultaneously improve the survival rate of osteoblasts and the amount of bone mineralization.

[0026] Preferably, the step of adhering and fixing the umbilical cord layer to the gel layer to obtain the biorepair membrane also includes: placing the mold sandwiched between the umbilical cord layer and the gel layer at a temperature of -10°C to -22°C for 2h to 6h, then placing it at a temperature of 0°C to 10°C for 2h to 6h for freeze-thaw treatment, and after 1 to 3 freeze-thaw cycles, freezing at -20°C for 2h, -80°C for 4h, -70°C to -80°C for 2h to 14h, and vacuum freeze-drying at a temperature of -80±5°C for 4h to 8h to obtain the biorepair membrane. The beneficial effects are as follows: during the compression freeze-drying process, the tissue is sequentially frozen at -20°C for 2 hours, -80°C for 4 hours, -70°C to -80°C for 2 hours to 14 hours, and vacuum freeze-dried at -80±5°C for 4 hours to 8 hours, i.e., gradient cooling and freezing is performed, thereby avoiding damage to the tissue structure caused by a too rapid temperature drop, thereby retaining the double-layer porous structure of the umbilical cord tissue; and through repeated freeze-thawing treatments, the gel layer is adsorbed into the micropores of the loose layer of the umbilical cord layer, thereby enhancing the adhesion between the gel layer and the umbilical cord layer, i.e., greatly improving the bonding strength between the fitting interfaces, thereby solving the problem of insufficient bonding strength between the membrane layers and easy delamination in the prior art.

[0027] Preferably, the step of trimming the umbilical cord tissue to be shaped into an umbilical cord layer with a sheet structure includes: in an environment with a temperature of 11°C to 15°C, washing the umbilical cord tissue to be shaped with a cleaning solution, trimming it into sheets, and washing it with deionized water 1 to 3 times to obtain the umbilical cord layer, wherein the washing temperature is 11°C to 15°C and the washing time is 15 to 20 minutes. The beneficial effect is that the umbilical cord tissue is washed with a cleaning solution to remove blood stains and damaged cells, and is rinsed with deionized water to keep the umbilical cord layer moist to facilitate adhesion to the gel layer. By setting the processing environment temperature of the umbilical cord layer to 11°C to 15°C and the washing time to 15 to 20 minutes, that is, by quickly processing in a low temperature environment, the natural active ingredients of the umbilical cord are retained to the greatest extent.

[0028] Preferably, the crosslinking agent is any one or two of 1-ethyl-(3-dimethylaminopropyl)carbodiimide, N-hydroxysuccinimide, genipin and formaldehyde. The beneficial effect is that the crosslinking agent is conducive to further improving the mechanical properties of the gel layer.

[0029] More preferably, the crosslinking agent is a mixed solution of 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and N-hydroxysuccinimide (NHS), which has the beneficial effect of further improving the mechanical properties of the gel layer, that is, effectively improving the mechanical properties of the bioremediation membrane.

[0030] Preferably, the concentration of the calcium chloride solution is 1% to 5%. This has the beneficial effect of allowing calcium ions to achieve controlled gelation within the sodium alginate. Chitosan solution is then added to the resulting matrix for acidification to release cations, thereby better controlling the gel properties and forming a homogeneous gel. Increasing the calcium ion concentration improves the cross-linking effect on the porous material and increases the material stability. However, gel layer scaffolds with higher calcium ion content tend to be more brittle. Therefore, a calcium chloride solution concentration of 1% to 5% is optimal.

[0031] Preferably, the steps of covering one side of the dense layer in the umbilical cord layer on the smooth side of the mold, adhering one side of the gel layer to one side of the loose layer in the umbilical cord layer, and then covering the indentation surface of another mold on the other side of the gel layer are repeated, and 2 to 6 layers of the umbilical cord layer and the gel layer are stacked in the order of the mold, the umbilical cord layer, the gel layer, and another mold to obtain a 2 to 6-layer biorepair membrane. Its beneficial effect is that the number of stacked layers of the biorepair membrane is generally 2 to 6 layers, which avoids the excessive weight of the mold causing the biorepair membrane to be freeze-dried to be deformed by compression, while reducing the energy consumption required for freeze-drying. The biorepair membrane obtained after compression and freeze-drying has two structures, an indentation surface and a smooth surface. The indentation surface can fit tightly with the tissue defect, blocking the ingrown soft tissue cells from the outside, and achieving a good therapeutic effect.

[0032] Preferably, the steps of preparing sodium alginate solution, chitosan solution and hydroxyapatite solution respectively include: weighing sodium alginate, dissolving it in deionized water and stirring it for 1h to 4h to obtain the sodium alginate solution; weighing chitosan, dissolving it in a dilute acid solution with a concentration of 1wt% to 2wt% and stirring it for 1h to 4h to obtain the chitosan solution; weighing hydroxyapatite, placing it in deionized water, and ultrasonically mixing it for 0.5h to 2h to obtain the hydroxyapatite solution. Its beneficial effect is that the ultrasonic method is conducive to mixing hydroxyapatite with other solutions in the subsequent process, and can make the hydroxyapatite uniformly dispersed in the polymer hydrogel matrix, that is, it can solve the problem of uneven dispersion of hydroxyapatite caused by high collagen viscosity or sticky blocks formed by collagen aggregation in existing collagen repair membranes, and the dispersion conditions are too intense and harsh, thereby affecting the molecular structure of collagen. It can also play a role in slowly releasing calcium ions to promote the proliferation and differentiation of bone cells during use.

[0033] Preferably, the cleaning solution is any one or more of sterile physiological phosphate buffer solution, sterile sodium chloride injection and purified water. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 Schematic diagram of a longitudinal section of a double-layer structure of the bioremediation membrane of the present invention obtained by scanning electron microscopy;

[0035] Figure 2 This is a schematic diagram of an electron microscope scanning of the umbilical cord layer in the bioremediation membrane of the present invention;

[0036] Figure 3 This is a schematic diagram of an electron microscope scanning of the gel layer in the bioremediation membrane of the present invention;

[0037] Figure 4 A schematic diagram of a mold according to a first embodiment of the present invention;

[0038] Figure 5 A schematic diagram of a mold according to a second embodiment of the present invention;

[0039] Figure 6 for Figure 5 An enlarged schematic diagram of the structure of the surface of the first layer in the mold shown;

[0040] Figure 7 for Figure 5 The structure of the surface of the second layer in the mold is shown in an enlarged schematic diagram. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with ordinary skills in the field to which the invention belongs. The words "including" and similar words used in this article mean that the elements or objects appearing before the word cover the elements or objects listed after the word and their equivalents, without excluding other elements or objects.

[0042] In addition, if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturers. All reagents or instruments without manufacturer's indication are common commercial products and can be purchased in the market.

[0043] Hydroxyapatite, the primary inorganic component of human bones and teeth, has been shown to exhibit excellent biocompatibility, high strength, and toughness, as well as its ability to conduct bone growth. It is widely used clinically for bone defect repair and plastic surgery. Currently, research has been conducted on composite biorepair membranes incorporating hydroxyapatite to improve the osteogenic properties of guided bone regeneration membranes. However, these methods still have limitations, including stringent operating conditions associated with electrochemical deposition and plasma spraying, long timescales associated with mineralization, uneven inorganic distribution associated with coating, collagen structural damage associated with blending, rapid hydroxyapatite loss, and the lack of sustained-release properties.

[0044] To overcome the problems existing in the prior art, the embodiments of the present invention provide a biorepair membrane and a preparation method thereof. By constructing a biorepair membrane composite of umbilical cord and hydroxyapatite, the problems that the repair membrane materials in the prior art are thin, easy to tear, have insufficient bone conductivity and mechanical properties, and are not suitable for repairing oral defects and bone defects alone are solved.

[0045] To achieve the above-mentioned purpose, the biorepair membrane and preparation method thereof of the present invention include a gel layer and an umbilical cord layer; the gel layer is formed by cross-linking hydroxyapatite, chitosan and sodium alginate; the umbilical cord layer is adhered to one side of the gel layer, and the umbilical cord layer is a sheet structure composed of umbilical cord tissue, and the umbilical cord tissue is formed from the umbilical cord by mechanically removing vascular cells.

[0046] Specifically, the biorepair membrane is formed by cross-linking hydroxyapatite, chitosan and sodium alginate through the gel layer, and the umbilical cord layer is adhered to one side of the gel layer. The umbilical cord layer is a sheet structure composed of umbilical cord tissue, and the umbilical cord tissue is formed in the umbilical cord by mechanically removing vascular cells. The various natural active ingredients retained by the umbilical cord layer can improve the healing ability of wounds and reduce scars produced after surgery; the hydroxyapatite is similar to the composition and structure of bones, has high strength and toughness, can simultaneously improve the survival rate and bone mineralization of osteoblasts, and guide bone defect repair, sodium alginate and chitosan are natural polymer materials with a wide source, similar to the extracellular matrix, the polymer hydrogel matrix scaffold composed of sodium alginate and chitosan has significant effects in antibacterial, hemostasis, promoting osteoblast adhesion, proliferation and the formation of mineralized bone matrix, and can form excellent properties such as interpenetrating or semi-interpenetrating networks in the polymer hydrogel matrix, and the double-network structure gel scaffold can enhance the hydrogel The mechanical properties of the biorepair membrane allow it to adhere closely to the surface of the tissue defect and maintain its integrity after absorbing liquid and swelling without causing the membrane to deform or shift. At the same time, the hydrogel is a good carrier that can load inorganic materials and bioactive substances and has the ability of controlled release. The multifunctional group characteristics of the hydrogel molecules make it easy to functionalize, thereby improving its effectiveness as a scaffold and carrier. That is, the biorepair membrane simultaneously possesses the natural bioactive components of the umbilical cord, the high osteogenic performance and osteoconductive activity of hydroxyapatite, and the excellent mechanical properties of sodium alginate and chitosan, so that the natural active components contained in the biorepair membrane can promote and induce cell proliferation and differentiation, achieve rapid vascularization and repair and regeneration of the defect area, and have good bioactivity, biodegradability, tissue adhesion, osteoconductivity and mechanical properties, good biocompatibility, no cytotoxicity, and no immunogenicity; it solves the problems in the prior art that the repair membrane material is thin and easy to tear, and has insufficient osteoconductivity and mechanical properties, making it unsuitable for use as a sole repair for oral defects and bone defects.

[0047] Figure 1 Schematic diagram of a longitudinal section of a double-layer structure of the bioremediation membrane of the present invention obtained by scanning electron microscopy; Figure 2 This is a schematic diagram of an electron microscope scanning of the umbilical cord layer in the bioremediation membrane of the present invention; Figure 3 Schematic diagram of electron microscope scanning of the gel layer in the bioremediation membrane of the present invention.

[0048] like Figure 1As shown, the bioremediation membrane is a double-layer structure. Figure 2 As shown in FIG, the umbilical cord layer has a dense structure and a small pore size. It can be seen that the umbilical cord layer retains the natural dense collagen fiber structure of the umbilical cord, which is used to face the soft tissue, is conducive to supporting the formation of soft tissue, and can effectively prevent fibroblasts and epithelial cells from growing into the bone defect area, and prevent soft tissue from growing into the bone defect area. In addition, the various natural active ingredients retained in the umbilical cord layer can improve the healing ability of gum wounds and reduce postoperative scars. Figure 3 As shown, the gel layer has a loose structure and a larger pore size than that of the umbilical cord layer. When applied to a tissue defect, it can effectively guide bone tissue regeneration.

[0049] In some embodiments of the present invention, the biorepair membrane is applied to bone tissue repair and oral soft tissue repair. It has a wide range of applications and strong versatility. When placed between oral soft tissue and bone defects, or between bone tissue and bone defects, the biorepair membrane can create a relatively closed bone regeneration environment. The biorepair membrane, facing the oral soft tissue or bone tissue, can block soft tissue cells with faster migration speeds from entering the bone defect area, thereby providing a good barrier protection. Furthermore, the hydroxyapatite in the gel layer of the biorepair membrane promotes osteogenesis and improves the mechanical properties of the biorepair membrane. The bioactive substances in the umbilical cord layer of the biorepair membrane can effectively promote soft tissue repair and regeneration, making the biorepair membrane applicable to oral soft tissue repair and bone tissue repair.

[0050] In some embodiments of the present invention, when the biorepair membrane is applied to oral soft tissue repair, the mass ratio of the chitosan to the sodium alginate is (1:1) to (1:3), and the concentration of hydroxyapatite in the polymer hydrogel matrix composed of the chitosan and sodium alginate is 0.1% (w / v) to 0.3% (w / v). Sodium alginate and chitosan have good biocompatibility, biodegradability, and antibacterial properties, and hydroxyapatite can ensure the mechanical and osteogenic properties of the biorepair membrane. Within this ratio range, cross-linking is sufficient, the surface of the gel layer is smoother and more regular in shape, and the pore size distribution in the biorepair membrane is uniform, resulting in a smooth morphology. If the hydroxyapatite content is too high, the freeze-dried biorepair membrane will become brittle and its morphology will not be well maintained.

[0051] In some embodiments of the present invention, when the biorepair membrane is applied to bone tissue repair, the mass ratio of chitosan to sodium alginate is (1:1) to (1:3), and the concentration of hydroxyapatite in the polymer hydrogel matrix composed of chitosan and sodium alginate is 0.2% (w / v) to 0.4% (w / v). Sodium alginate and chitosan have good biocompatibility, biodegradability, and antibacterial properties, and hydroxyapatite can ensure the mechanical and osteogenic properties of the biorepair membrane. Within this ratio range, cross-linking is sufficient, the surface of the gel layer is smoother and more regular in shape, and the pore size distribution in the biorepair membrane is uniform, resulting in a flat morphology. If the hydroxyapatite content is too high, the freeze-dried biorepair membrane will become brittle and its morphology will not be well maintained. This concentration of hydroxyapatite is beneficial for improving the support properties of the formed biorepair membrane, resulting in better bone tissue repair. In the case of a large area of ​​bone defect, the mechanical properties of the umbilical cord layer itself cannot provide sufficient support, and it is easily deformed by squeezing of soft tissues such as muscles, making it difficult to achieve a good therapeutic effect. Therefore, when the biorepair membrane is used for bone tissue repair, the concentration of hydroxyapatite is higher, which is beneficial to improving the mechanical properties of the biorepair membrane, so as to better promote bone repair.

[0052] In some embodiments of the present invention, the weight ratio of the hydroxyapatite, the chitosan, and the sodium alginate is (1:4:4) to (4:10:15).

[0053] In some specific embodiments of the present invention, when the biorepair membrane is used for oral soft tissue repair, the weight ratio of the hydroxyapatite, the chitosan, and the sodium alginate is 1.5:1:0.45.

[0054] In some specific embodiments of the present invention, when the biorepair membrane is used for bone tissue repair, the weight ratio of the hydroxyapatite, the chitosan, and the sodium alginate is 1.5:1:0.6.

[0055] In some embodiments of the present invention, the side of the umbilical cord layer facing away from the gel layer is a smooth surface, and the side of the gel layer facing away from the umbilical cord layer is an indentation surface, and the indentation surface is provided with a convex structure and a concave structure. The double-sided structure can fit well with the part to be repaired, provide a relatively closed tissue growth environment, provide good space and time for bone regeneration, and promote tissue repair and regeneration. Among them, the convex structure and the concave structure of the indentation surface can effectively increase the degree of fit and contact surface area between the biorepair membrane and the part to be repaired, improve the fit between the biorepair membrane and the tissue defect, and improve clinical use and treatment effects. The biorepair membrane has an indentation surface and a smooth surface. The double-sided structure not only fits well with the part to be repaired, can selectively guide cell growth, and can degrade synchronously with the reconstruction of the new tissue. The present invention solves the problem in the prior art that there is a gap between the biorepair membrane with smooth surfaces on both sides and the tissue defect, which causes fibroblasts and epithelial cells with faster growth and migration rates to enter the bone defect area, forming competitive inhibition with osteoblasts with slower growth and migration rates, and adversely affecting the healing of bone tissue.

[0056] In some embodiments of the present invention, the gel layer and the umbilical cord layer are adhered and fixed by freeze-drying through a mold. The mold comprises a first surface and a second surface disposed opposite each other. The first surface is an indentation surface adapted to the indentation surface and is provided with a raised structure and a recessed structure. The second surface is a smooth surface adapted to the smooth surface. This allows the mold to be used to freeze-dry a biorepair membrane into a membrane with different structures on both sides. Specifically, the indentation surface provided with the raised and recessed structures results in one surface of the freeze-dried biorepair membrane having raised and recessed structures. This effectively increases the biorepair membrane's conformity to the repaired site and its contact surface area, improving its fit with the tissue defect and enhancing clinical efficacy. This solves the problem in prior art where both surfaces of the biorepair membrane are smooth and flat, resulting in a gap between the membrane and the tissue defect, causing faster-growing and migrating fibroblasts and epithelial cells to enter the bone defect, competitively inhibiting slower-growing and migrating osteoblasts and adversely affecting bone tissue healing.

[0057] In some embodiments of the present invention, the umbilical cord is an allogeneic umbilical cord. Allogeneic umbilical cord has a porous, double-layer structure, with one layer of densely packed collagen fibers and another layer of loosely packed collagen fibers. It also contains multiple bioactive components, exhibits low immunogenicity, and has unique biological properties that promote cell attachment, tissue regeneration, and healing, making it of great significance in clinical applications.

[0058] In some embodiments of the present invention, the umbilical cord tissue is derived from the human body. The use of human umbilical cord tissue as the basal layer breaks the limitation of using animal-derived raw materials to prepare biorepair membranes, which can effectively prevent patients from having rejection reactions. The umbilical cord contains basic fibroblast growth factor, insulin-like growth factor, platelet-derived growth factor, and transforming growth factor, etc., which can serve as a sustained-release carrier of growth factors to promote cell proliferation and osteogenic activity. In addition, human umbilical cord has low immunogenicity, and its natural active ingredients are mainly composed of collagen, glycoproteins, mucopolysaccharides, and growth factors. It can not only provide cells with a biomimetic three-dimensional support carrier, but also promote the migration, proliferation, and differentiation of host cells through the interaction of various proteins and growth factors with the host, thereby promoting tissue regeneration and repair.

[0059] In some embodiments of the present invention, the umbilical cord layer has a double-layer porous structure, comprising a dense layer and a loose layer, wherein the pore size of the dense layer is smaller than that of the loose layer, the loose layer is adhered and fixed to the gel layer, and the dense layer is provided with the smooth surface. The biorepair membrane is used to be placed between the oral soft tissue and the bone defect to create a relatively closed bone regeneration environment; therefore, the dense layer with a small pore size facing the soft tissue can block the fibroblasts and epithelial cells with faster migration speeds from entering the bone defect area, thereby acting as a barrier; compared to the prior art double-layer membrane structure in which the two different layers are simply fixed by pressing, the loose layer in the present invention is adhered to the gel layer, and through repeated freeze-thaw treatment, the gel layer is adsorbed into the micropores of the loose layer of the umbilical cord layer, thereby enhancing the adhesion between the gel layer and the umbilical cord layer, that is, greatly improving the bonding strength between the bonding interfaces, solving the problem of insufficient bonding strength between the membrane layers and easy delamination in the prior art.

[0060] In some embodiments of the present invention, the pore size of the loose layer is 20μm to 100μm. The umbilical cord itself has a natural double-sided structure. The dense layer retains the natural collagen fiber dense structure of the umbilical cord, which is used to face the soft tissue, effectively preventing fibroblasts and epithelial cells from growing into the bone defect area, supporting soft tissue formation, and preventing soft tissue from growing into the bone defect area; the collagen in the loose layer is relatively sparsely arranged and has a certain pore size, which can achieve close integration with the gel layer in some areas during repeated freezing and thawing, and realize the preparation of a double-layer membrane that does not delaminate after rehydration. Therefore, when applied to tissue defects, the dense layer and the loose layer can effectively play their respective roles.

[0061] The method for preparing the bioremediation membrane of the present invention comprises the following steps:

[0062] Providing an original umbilical cord, mechanically removing blood vessels in the original umbilical cord to form umbilical cord tissue to be shaped, and trimming the umbilical cord tissue to be shaped into an umbilical cord layer with a sheet-like structure;

[0063] preparing a sodium alginate solution, a chitosan solution, and a hydroxyapatite solution respectively, uniformly mixing the chitosan solution, the sodium alginate solution, and the hydroxyapatite solution to obtain a gel solution, and then subjecting the gel solution to a cross-linking reaction to obtain a gel layer;

[0064] The umbilical cord layer is adhered and fixed to the gel layer to prepare the biorepair membrane.

[0065] Specifically, the various natural active ingredients retained in the umbilical cord layer can improve the healing ability of gingival wounds and reduce scars produced after surgery; the hydroxyapatite is similar to the composition and structure of bones, has high strength and toughness, can simultaneously improve the survival rate of osteoblasts and the amount of bone mineralization, and guide bone defect repair; sodium alginate and chitosan are natural polymer materials with a wide source, similar to the extracellular matrix, and can form interpenetrating or semi-interpenetrating networks and other excellent properties in the polymer hydrogel matrix made of sodium alginate and chitosan; the double-network structure of the gel scaffold can enhance the mechanical properties of the hydrogel, so that it can maintain its integrity after absorbing liquid and swelling on the surface of the tissue defect without causing the membrane to deform or shift, so that the prepared biorepair membrane contains natural active ingredients that can promote the induction of cell proliferation and differentiation, achieve rapid vascularization and repair and regeneration of the defect area, and has good biological activity, biodegradability, tissue adhesion and mechanical properties, good biocompatibility, no cytotoxicity, and no immunogenicity.

[0066] In some embodiments of the present invention, the step of uniformly mixing the chitosan solution, the sodium alginate solution and the hydroxyapatite solution to obtain a gel solution comprises: dripping the chitosan solution into the sodium alginate solution at a rate of 1 mL / min to 2 mL / min, and stirring and mixing to obtain a polymer hydrogel matrix; adding the hydroxyapatite solution into the polymer hydrogel matrix at a rate of 1 mL / min to 2 mL / min, and stirring and mixing to obtain the gel solution. The configuration of the gel solution is to first prepare the sodium alginate solution, and then slowly drip the chitosan solution into the sodium alginate solution. This order of addition can avoid the problem of mutual adhesion and poor connectivity of the pores inside the material, thereby obtaining a porous membrane material with suitable pore structure, good elasticity and mechanical properties, and the pore structure is evenly distributed, without adhesion, and there is no problem of uneven size distribution.

[0067] In some embodiments of the present invention, the step of cross-linking the gel solution to obtain a gel layer includes: ultrasonically removing bubbles from the gel solution and then vacuum freeze-drying for 12 to 24 hours to obtain a gel membrane material; soaking the gel membrane material in a calcium chloride solution for cross-linking for 0.1 to 1 hour, soaking it in a cross-linking agent solution for 1 to 4 hours, and then soaking and washing it with deionized water 1 to 3 times, with each soaking and washing time being 5 to 10 minutes, to obtain the gel layer. Ultrasonication is beneficial for uniformly dispersing the hydroxyapatite in the polymer hydrogel matrix, which can solve the problems of uneven dispersion of hydroxyapatite and excessively harsh dispersion conditions in existing collagen repair membranes, which affect the molecular structure of collagen due to high collagen viscosity or adhesive blocks formed by collagen aggregation. It can also play a role in slowly releasing calcium ions during use to promote the proliferation and differentiation of bone cells. The calcium ions in the calcium chloride solution can complex and cross-link with the sodium alginate to form an egg-box structure, and then form a cross-linked network structure through group accumulation, so that the gel solution is converted into a hydrogel, so that the prepared gel layer has optimal stability and adsorption capacity; soaking in the cross-linking agent can further improve the mechanical properties of the gel layer, and soaking and washing with deionized water 1 to 3 times, and each soaking and washing time is 5 minutes to 10 minutes to wash away excess cross-linking agent.

[0068] In some embodiments of the present invention, the step of adhering and fixing the umbilical cord layer to the gel layer to obtain the biorepair membrane includes: in an environment with a temperature of 11°C to 15°C, covering one side of the dense layer in the umbilical cord layer on the smooth surface of the mold, adhering one side of the gel layer to one side of the loose layer in the umbilical cord layer, and then covering the indentation surface of another mold on the other side of the gel layer. The processing environment temperature of the umbilical cord layer is 11°C to 15°C, that is, rapid processing in a low-temperature environment can retain the natural active ingredients of the umbilical cord to the greatest extent; after the mold pressing and freeze-drying treatment, the biorepair membrane has a double-sided structure with an indented surface and a smooth surface, and the loose layer of the sheet umbilical cord layer is bonded to the gel layer. After subsequent freeze-thaw cycles, cross-linking with a cross-linking agent and vacuum freeze-drying treatment, the loose layer and the gel layer can be more deeply integrated, without obvious stratification, and the structural continuity is good; the surface of the part to be repaired is usually not smooth, and the presence of the indentation structure can effectively increase the degree of fit between the repair membrane and the part to be repaired and the contact surface area, which is beneficial to promoting tissue healing; and the gel layer with hydroxyapatite covers the indentation surface of the mold, even if the gel layer has an indentation surface, so that the indentation surface of the gel layer with hydroxyapatite faces the bone defect, which can simultaneously improve the survival rate of osteoblasts and the amount of bone mineralization.

[0069] In some embodiments of the present invention, the step of adhering and fixing the umbilical cord layer to the gel layer to obtain the biorepair membrane also includes: placing the mold sandwiched between the umbilical cord layer and the gel layer at a temperature of -10°C to -22°C for 2h to 6h, then placing it at a temperature of 0°C to 10°C for 2h to 6h for freeze-thaw treatment, and after 1 to 3 freeze-thaw cycles, freezing at -20°C for 2h, freezing at -80°C for 4h, freezing at -70°C to -80°C for 2h to 14h, and vacuum freeze-drying at -80±5°C for 4h to 8h to obtain the biorepair membrane. The beneficial effects are as follows: during the compression freeze-drying process, the tissue is sequentially frozen at -20°C for 2 hours, -80°C for 4 hours, -70°C to -80°C for 2 hours to 14 hours, and vacuum freeze-dried at -80±5°C for 4 hours to 8 hours, i.e., gradient cooling and freezing is performed, thereby avoiding damage to the tissue structure caused by a too rapid temperature drop, thereby retaining the double-layer porous structure of the umbilical cord tissue; and through repeated freeze-thawing treatments, the gel layer is adsorbed into the micropores of the loose layer of the umbilical cord layer, thereby enhancing the adhesion between the gel layer and the umbilical cord layer, i.e., greatly improving the bonding strength between the fitting interfaces, thereby solving the problem of insufficient bonding strength between the membrane layers and easy delamination in the prior art.

[0070] In some embodiments of the present invention, the step of trimming the umbilical cord tissue to be shaped into an umbilical cord layer with a sheet structure includes: in an environment with a temperature of 11°C to 15°C, washing the umbilical cord tissue to be shaped with a cleaning solution, trimming it into sheets, and washing it with deionized water 1 to 3 times to produce the umbilical cord layer, wherein the washing temperature is 11°C to 15°C and the washing time is 15 to 20 minutes. The beneficial effect of this method is that the umbilical cord tissue is washed with a cleaning solution to remove blood stains and damaged cells, and is rinsed with deionized water to keep the umbilical cord layer moist to facilitate adhesion to the gel layer. By setting the processing environment temperature of the umbilical cord layer to 11°C to 15°C and the washing time to 15 to 20 minutes, the umbilical cord layer is quickly processed in a low temperature environment to maximize the preservation of the natural active ingredients of the umbilical cord.

[0071] In some embodiments of the present invention, the crosslinking agent is any one or two of 1-ethyl-(3-dimethylaminopropyl)carbodiimide, N-hydroxysuccinimide, genipin, and formaldehyde, which is beneficial for further improving the mechanical properties of the gel layer, that is, effectively improving the mechanical properties of the bioremediation membrane.

[0072] In some embodiments of the present invention, the crosslinking agent is a mixed solution of 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and N-hydroxysuccinimide (NHS). This can further enhance the mechanical properties of the gel layer. EDC crosslinkers are non-toxic and biocompatible, and many research reports have shown that EDC-crosslinked collagen-based scaffolds exhibit superior cytocompatibility. Combining EDC with NHS improves crosslinking efficiency.

[0073] In some embodiments of the present invention, the concentration of the calcium chloride solution is 1% to 5%. Calcium ions can achieve controlled gelation within the sodium alginate. Chitosan solution is then added to the resulting matrix for acidification to release cations, thereby better controlling the gel properties and forming a homogeneous gel. Increasing the calcium ion concentration improves the cross-linking effect on the porous material and increases material stability. However, gel-layer scaffolds with higher calcium ion content tend to be more brittle. Therefore, a calcium chloride solution concentration of 1% to 5% is optimal.

[0074] In some embodiments of the present invention, the steps of covering one side of the dense layer in the umbilical cord layer on the smooth surface of the mold, adhering one side of the gel layer to one side of the loose layer in the umbilical cord layer, and then covering the indentation surface of another mold on the other side of the gel layer are repeated, and 2 to 6 layers of the umbilical cord layer and the gel layer are stacked in the order of the mold, the umbilical cord layer, the gel layer, and another mold to obtain a 2 to 6-layer biorepair membrane. The number of stacked layers of the biorepair membrane is generally 2 to 6 layers, to avoid the excessive weight of the mold causing the biorepair membrane to be freeze-dried to be deformed by compression, while reducing the energy consumption required for freeze-drying. The biorepair membrane obtained after compression and freeze-drying has two structures, an indentation surface and a smooth surface. The indentation surface can fit tightly with the tissue defect, blocking the ingrown soft tissue cells from the outside, and achieving a good therapeutic effect.

[0075] Specifically, one side of the dense layer in the first umbilical cord layer is covered on the smooth surface of the first mold, one side of the first gel layer is tightly adhered to one side of the loose layer of the first umbilical cord layer, and then the indentation surface of the second mold is covered on the other side of the first gel layer; that is, two molds are used to press the umbilical cord layer and the gel layer in the same biorepair membrane; using the above-mentioned stacking method, 2-6 sheets of the biorepair membrane can be produced by stacking and pressing 3 to 7 molds layer by layer.

[0076] In some specific embodiments of the present invention, one side of the dense layer in the first umbilical cord layer is covered on the smooth surface of the first mold, one side of the first gel layer is tightly adhered to one side of the loose layer of the first umbilical cord layer, and the indentation surface of the second mold is covered on the other side of the first gel layer, one side of the dense layer in the second umbilical cord layer is covered on the smooth surface of the second mold, one side of the second gel layer is tightly adhered to one side of the loose layer of the second umbilical cord layer, and the indentation surface of the third mold is covered on the other side of the second gel layer, so that two biorepair membranes can be prepared.

[0077] In some embodiments of the present invention, the steps of preparing sodium alginate solution, chitosan solution and hydroxyapatite solution respectively include: weighing sodium alginate, dissolving it in deionized water and stirring it for 1 hour to 4 hours to obtain the sodium alginate solution; weighing chitosan, dissolving it in a dilute acid solution with a concentration of 1wt% to 2wt% and stirring it for 1 hour to 4 hours to obtain the chitosan solution; weighing hydroxyapatite, placing it in deionized water, and ultrasonically mixing it for 0.5 hours to 2 hours to obtain the hydroxyapatite solution. Ultrasonication is beneficial for mixing hydroxyapatite with other solutions in subsequent processes, and can make the hydroxyapatite uniformly dispersed in the polymer hydrogel matrix, that is, it can solve the problems of uneven dispersion of hydroxyapatite caused by high collagen viscosity or adhesive blocks formed by collagen aggregation in existing collagen repair membranes, and the dispersion conditions are too intense and harsh, thereby affecting the molecular structure of collagen. It can also play a role in slowly releasing calcium ions to promote the proliferation and differentiation of bone cells during use. Specifically, hydroxyapatite, also known as calcium hydroxyapatite, is a major inorganic component of human and animal bones. It has a certain solubility in the body and can release inorganic ions to participate in metabolism. This stimulates or induces bone growth, promotes the repair of defective tissue, and exhibits biological activity. However, hydroxyapatite is slightly soluble in water, and directly adding hydroxyapatite powder may require long stirring times and high power for relatively uniform mixing. Therefore, ultrasonic treatment before adding it to the polymer hydrogel matrix allows for more uniform dispersion.

[0078] In some embodiments of the present invention, the dilute acid solution is acetic acid solution or the like.

[0079] In some embodiments of the present invention, chitosan is weighed and dissolved in a glacial acetic acid solution with a concentration of 1 wt% to 2 wt% and stirred for 1 h to 4 h to prepare the chitosan solution.

[0080] In some embodiments of the present invention, the cleaning solution is any one or more of sterile physiological phosphate buffer solution, sterile sodium chloride injection and purified water.

[0081] In some embodiments of the present invention, the preparation of the umbilical cord layer includes the steps of: cleaning the original umbilical cord, removing blood vessels, cutting it into a desired shape, and finally washing it with deionized water for 1 to 3 times for use.

[0082] In some embodiments of the present invention, the preparation of the gel layer, i.e., the hydroxyapatite-loaded sodium alginate and chitosan gel scaffold layer, comprises the following steps:

[0083] S110: Weigh 0.4 g to 1.5 g of sodium alginate, dissolve it in deionized water, and stir for 2 h to obtain a sodium alginate solution;

[0084] S120: Weigh 0.4 g to 1 g of chitosan and dissolve it in a 1 wt% to 2 wt% glacial acetic acid solution and stir for 2 h to obtain a chitosan solution;

[0085] S130: Weigh 0.1 g to 0.4 g of hydroxyapatite, place in deionized water, and mix thoroughly by ultrasonication for 0.5 h to obtain a hydroxyapatite solution;

[0086] S140: slowly adding the chitosan solution prepared in step S120 to the sodium alginate solution prepared in step S110, and continuously stirring and mixing after the addition is completed within 0.5 h to obtain a polymer hydrogel matrix; then, adding the hydroxyapatite solution prepared in step S130 to the polymer hydrogel matrix at a dripping rate of 2 mL / min, stirring and mixing to obtain the gel solution, ultrasonically removing bubbles in the gel solution, and then freeze-drying in a vacuum freeze dryer for 12 to 24 h to obtain a gel membrane material;

[0087] S150: soaking the gel membrane material prepared in step S140 in a 2% calcium chloride solution for crosslinking for 0.1 to 1 hour, then soaking it in a crosslinker solution mixed with EDC and NHS for 1 to 4 hours, and finally soaking and washing it with deionized water for 1 to 3 times for use.

[0088] In some embodiments of the present invention, the preparation of a biorepair membrane composite of umbilical cord and hydroxyapatite includes the steps of: covering one side of the dense layer in the umbilical cord layer on the smooth surface of the mold, tightly adhering one side of the gel layer to the other side of the umbilical cord layer, that is, one side of the loose layer, and then covering the other side of the gel layer with the indentation surface of the other mold; the umbilical cord and the gel layer together with the mold are placed at a temperature of -20°C for 2 hours, and then placed at a temperature of 4°C for 2 hours, and freeze-thaw cycle treatment is carried out twice under these conditions, successively freezing at -20°C for 2 hours, freezing at -80°C for 4 hours, freezing in a refrigerator at -80°C for 4 hours, and vacuum freeze-drying at -80°C for 4 hours to 8 hours. After cutting, an umbilical cord / hydroxyapatite composite biorepair membrane with a double-sided structure can be obtained.

[0089] In some specific embodiments 1 of the present invention, the method for preparing the bioremediation membrane comprises the following steps:

[0090] S1. Preparation of umbilical cord layer:

[0091] S11, adding the original umbilical cord and purified water at a material-to-liquid ratio of at least 1:5 by mass to wash the original umbilical cord twice;

[0092] S12. Selecting annular drill bits of different inner diameters according to the diameter of the blood vessels in the original umbilical cord to remove blood vessels in the original umbilical cord to obtain umbilical cord tissue to be reshaped; then cutting the umbilical cord into flat slices along the axial direction of the umbilical cord to trim the umbilical cord tissue to be reshaped into a sheet-like structure of umbilical cord tissue; specifically, the sheet-like structure of umbilical cord tissue must be greater than 3 cm in width and greater than 6 cm in length; the umbilical cord epithelial surface must not have any damage greater than 1 cm, and must not have more than three damages less than 1 cm, and the intact area must be no less than 3 cm x 3 cm;

[0093] S13, soak and clean with deionized water once for later use;

[0094] S2. Preparation of gel layer:

[0095] S21, weighing 1.5 g of sodium alginate and dissolving it in 50 mL of deionized water and stirring for 2 h to obtain a sodium alginate solution;

[0096] S22, weighing 1 g of chitosan and dissolving it in 50 mL of 2 wt% glacial acetic acid solution and stirring for 2 h to obtain a chitosan solution;

[0097] S23, weighing 0.45 g of hydroxyapatite and placing it in 50 mL of deionized water, and mixing it by ultrasonication for 0.5 h to obtain a hydroxyapatite solution, which is conducive to mixing the hydroxyapatite with other solutions in subsequent processes;

[0098] S24, slowly adding the chitosan solution prepared in step S22 to the sodium alginate solution prepared in step S21 and continuously stirring and mixing to obtain a polymer hydrogel matrix; then, under stirring, adding the hydroxyapatite solution prepared in step S23 to the polymer hydrogel matrix solution at a dripping rate of 2 mL / min and stirring and mixing to obtain a gel solution;

[0099] S25, sonicating the gel solution prepared in step S24 for 0.5 h to remove bubbles in the gel solution, and then freeze-drying the solution for 12 h to obtain a gel film material;

[0100] S26, soaking the gel membrane material prepared in step S25 in a 2% calcium chloride solution for in-situ crosslinking for 0.2 h, then soaking it in a crosslinker solution mixed with EDC and NHS for 1 h, and finally soaking and washing it with deionized water three times for later use;

[0101] S3. Preparation of bioremediation membrane:

[0102] S31, covering one side of the dense layer of the umbilical cord layer obtained in step S1 on the smooth surface of the first mold, tightly adhering one side of the gel layer obtained in step S2 to the other side of the umbilical cord layer, i.e., one side of the loose layer, and then covering the other side of the gel layer with the indented surface of the second mold; that is, using two molds to press the umbilical cord layer and the gel layer in the same biorepair membrane;

[0103] S32. The pressed sample and the mold are then subjected to freeze-thaw cycle treatment, vacuum freeze drying, and sterilization treatment in sequence to obtain a biorepair membrane composed of umbilical cord and hydroxyapatite.

[0104] Specifically, in the step S2 of preparing the gel layer, the polymer hydrogel matrix made of sodium alginate and chitosan is non-cytotoxic and has antibacterial activity, so that the freeze-dried gel scaffold layer has a microporous structure and a certain permeability, which can effectively absorb wound exudate and avoid related infections caused by bacteria in the wound.

[0105] Specifically, in the step S2 of preparing the gel layer, the proportion and order of slowly adding the chitosan solution to the sodium alginate solution can obtain a porous gel membrane material with a smoother surface and a suitable pore structure. The reason for this phenomenon is that the chitosan dissolves more completely and mixes more evenly, the low-concentration solution will not be too sticky, and the ice crystals formed by freezing increase, thereby increasing the pore structure formed and the pores are enlarged.

[0106] Specifically, the ultrasonic treatment in step S23 and step S25 can effectively remove bubbles generated during the mixing process and evenly disperse the hydroxyapatite in the solution.

[0107] Specifically, in step S31, one side of the gel layer of the biorepair membrane is attached to the indentation surface of the first mold, and then the smooth surface of the second mold is covered on the umbilical cord layer side of the repair membrane, so that the biorepair membrane is clamped between the two molds. After pressing and freeze-drying, one surface of the gel layer is concave-convex, and even one surface of the biorepair membrane after pressing and freeze-drying forms a convex structure and a concave structure, thereby effectively increasing the degree of fit between the biorepair membrane and the part to be repaired and the contact surface area; the surface of one side of the dense layer in the umbilical cord layer is flat and smooth after pressing, so that it has a good mechanical barrier effect.

[0108] In some embodiments of the present invention, the crosslinker solution containing EDC and NHS in step S26 has a concentration of 1 mg / mL and a mass ratio of EDC to NHS of 4:1. The time and concentration of the crosslinker are selected to enhance the mechanical properties of the gel scaffold while preventing excessive crosslinking density that could render the gel scaffold excessively brittle. The EDC in the crosslinker can activate carboxyl groups within and between polysaccharide molecules to form carboxylic anhydrides. These anhydrides can then readily react with carboxyl groups within the polysaccharide to form ester groups, which, in turn, react with amino groups in the presence of NHS to form amides, thereby enhancing the thermal stability, morphological stability, and degradation resistance of the umbilical cord layer. During the crosslinking process, EDC and NHS act as intermediate reagents, ultimately forming urea compounds that can be washed away.

[0109] In some embodiments of the present invention, the cleaning temperature in step S11 is 12° C., and each cleaning of the umbilical cord tissue lasts 16 minutes to maximize the retention of bioactive components in the umbilical cord.

[0110] In some embodiments of the present invention, step S32 includes: placing the pressed sample together with the mold at a temperature of -20°C for 2 hours, and then placing it at a temperature of 4°C for 2 hours, which is regarded as a freeze-thaw treatment; after two freeze-thaw cycles under the above freeze-thaw treatment conditions, placing it in a refrigerator at a temperature of -80°C for 4 hours; and finally placing it in a vacuum freeze-drying environment at a vacuum degree of 20 Pa and a temperature of -80°C for 24 hours to produce the bioremediation membrane of the umbilical cord and hydroxyapatite composite, with a moisture content of no more than 20% after freeze-drying. Specifically, the freeze-thaw cycle makes the surface of the membrane material wet in a solid-liquid state, which is conducive to the close cross-linking and bonding of the umbilical cord layer and the gel layer to form a whole, thereby ensuring the stability of the structure during subsequent use and reducing the probability of delamination of the double-layer structure. Freeze-thaw cycles can prevent the temperature from dropping too quickly and damaging the tissue structure, effectively preserve the ultrastructure of the extracellular matrix, significantly improve the drying efficiency of the repair membrane, and obtain a more uniform pore structure, so that the biorepair membrane can maintain a certain sealing effect while allowing oxygen, blood, and bioactive substances to enter, promoting local cell growth and bone regeneration.

[0111] The bioremediation membrane prepared in Example 1 was rehydrated in 0.9% saline for 15-30 minutes. The results showed that the bioremediation membrane remained intact, with no delamination between the umbilical cord layer and the gel layer. This indicates that the umbilical cord layer and the gel layer remained tightly bonded in some areas during repeated freeze-thaw cycles, demonstrating that the present invention achieves the production of a bilayer membrane that does not delaminate after rehydration.

[0112] The mechanical properties of the bioremediation membrane prepared in Example 1 were tested according to the test conditions specified in GB / T5528-2009, Rubber, vulcanized or thermoplastic, Determination of tensile stress-strain properties, and GB / T1040.3-2006, Plastics, Determination of tensile properties, Part 3: Films and sheets. Three groups of samples were tested, and the test results are shown in Table 1. Table 1 shows that the bioremediation membranes exhibited an average suture strength of no less than 1 N, a tensile strength of no less than 0.5 MPa, and a tear strength of no less than 1 N.

[0113] Table 1

[0114]

[0115] In vitro degradation testing was performed on the biorepair membrane prepared in Example 1. The experimental results showed that the tissue retention rate of the biorepair membrane and the tissue retention rate of the original umbilical cord showed a similar trend over degradation time, indicating that the biorepair membrane has good degradation properties and can degrade synchronously with the reconstruction of new tissue.

[0116] The biorepair membrane prepared in Example 1 was tested for water absorption according to the standard YY / T 1794-2021, General Technical Requirements for Oral Collagen Membranes. Three groups of samples were tested, and the test results are shown in Table 2. As shown in Table 2, the average water absorption ratio of the biorepair membrane was 13.1. This high water absorption rate enables the biorepair membrane to adhere well to tissues, facilitating clinical use and enabling clinicians to combine it with other medications.

[0117] Table 2

[0118]

[0119] The host cell residue test was performed on the biorepair membrane prepared in Example 1. The biorepair membrane was sliced ​​and stained with HE. Microscopic observation showed that no vascular cells were left, and the potential risk was controlled at the lowest level.

[0120] The bioremediation membrane prepared in Example 1 was subjected to in vitro cytotoxicity testing in accordance with Section 5 of GB / T 16886.5-2003: Cytotoxicity Test for Determination of Cytotoxicity of the Bioremediation Membrane. Tests were performed on samples containing extracts at concentrations of 100%, 50%, 25%, and 12.5%, as well as a negative control group, a blank control group, and a positive control group. The test results are shown in Table 3. As shown in Table 3, there was no significant difference in the proliferation rate of mouse fibroblast L929 cells between the bioremediation membrane, the blank control, and the negative control. However, the L929 proliferation rate of the positive control was significantly lower than 10%, indicating that the bioremediation membrane exhibited good biocompatibility.

[0121] Table 3

[0122]

[0123] The biorepair membrane prepared in Example 1 was tested for active factors and components, and the various factors and total protein content of the umbilical cord layer and fresh umbilical cord in the biorepair membrane were determined. The data for various factors in the umbilical cord layer and fresh umbilical cord in the biorepair membrane are shown in Table 4. The total umbilical cord protein content of the umbilical cord layer in the biorepair membrane is shown in Table 5.

[0124] Table 4

[0125]

[0126] As shown in Table 5, the total umbilical cord protein content of the umbilical cord layer in the biorepair membrane is no less than 90% of the dry weight. As shown in Table 4, the content of various factors in the umbilical cord layer is not much different from that in the fresh original umbilical cord used as the raw material, indicating that the method of preparing the biorepair membrane of the present invention can retain its multiple natural active factor components and has more unique biological properties that promote healing than simple collagen membranes or decellularized matrix products.

[0127] Table 5

[0128]

[0129] In some embodiments of the present invention, the biorepair membranes were used in experimental experiments. Specifically, the experimental group used the biorepair membranes described herein to fill and repair extraction sockets in dogs, while the control group used the absorbable biomembrane Geistlich Bio-Gide to fill and repair extraction sockets in dogs. Postoperative Micro-CT data for the experimental and control groups are shown in Table 6.

[0130] Table 6

[0131]

[0132] Analysis of Table 6 shows that MicroCT scans revealed a significant increase in the bone volume fraction (BV / TV) of the biorepair membrane in the experimental group compared to the control group at 12 weeks, indicating a significant increase in bone mass due to greater bone anabolism than catabolism. Furthermore, postoperatively, the gingival condition at all implant sites in the experimental group was excellent, with no infection, inflammation, or other rejection symptoms, and no oral membrane exposure.

[0133] Figure 4 Schematic diagram of a mold according to a first embodiment of the present invention.

[0134] In some embodiments of the present invention, the mold is an integrally formed structure, and the mold includes a first surface and a second surface arranged opposite to each other. Figure 4 The first surface is an indentation surface 1, and the indentation surface 1 is provided with a convex structure (not marked in the figure) and a concave structure (not marked in the figure), and the second surface (not marked in the figure) is a smooth surface.

[0135] Figure 5 Schematic diagram of a mold according to a second embodiment of the present invention.

[0136] In some embodiments of the present invention, reference Figure 5 The mold comprises a first layer 11 and a second layer 12, which are fixedly overlapped in an upper and lower manner. The opposing surfaces of the first layer 11 and the second layer 12 are respectively a first surface 111 and a second surface (not shown). Both the first layer 11 and the second layer 12 are woven from 316L stainless steel wire. This has a simple structure, an easy manufacturing process, and low manufacturing costs. Furthermore, the corrosion resistance and weldability of stainless steel ensure that the mold has good stability and plasticity, as well as high mechanical strength.

[0137] Figure 6 for Figure 5 An enlarged schematic diagram of the structure of the surface of the first layer in the mold shown; Figure 7 for Figure 5 The structure of the surface of the second layer in the mold is shown in an enlarged schematic diagram.

[0138] In some embodiments of the present invention, reference Figure 6 and Figure 7 The first layer 11 is woven in a dense weave manner, so that the first surface 111 of the first layer 11 is an indentation surface, and the indentation surface is provided with the convex structure 101 and the concave structure 102 arranged in an orderly manner. The dense weave means that the warp and weft have different wire diameters and different mesh counts, and the characteristics are that the warp is sparse and the weft is dense, and the warp is thick and the weft is thin. The length direction is the warp, the width direction is the weft, and the length direction is as follows. Figure 6The direction indicated by A is shown in FIG. 1 , and the width direction is the direction perpendicular to A. The specific structure after dense weaving is as follows: Figure 6 As shown, its weaving method is conventional in the art and will not be described here. The second layer 12 is woven in a twill weaving method, so that the second surface (not shown in the figure) of the second layer 12 is a smooth surface with a relatively flat surface and dense and small pores. The twill weaving method refers to a weaving method in which each warp wire crosses above and below each two weft wires, and each weft wire crosses above and below each two warp wires. The specific structure after the twill weaving is as follows. Figure 4 As shown. The first layer 11, woven using the dense weave, exhibits excellent acid and alkali resistance, high temperature resistance, and strong pressure and wear resistance. The second layer 12, woven using the twill weave, exhibits a flat and smooth surface, strong corrosion resistance, and durability. The dense weave of the first layer 11 effectively forms the raised structures 101 and recessed structures 102 on its surface. The twill weave of the second layer 12 results in a smooth and even surface.

[0139] In some embodiments of the present invention, the stainless steel wire used to braid the first layer has a warp diameter of 0.2 mm to 0.28 mm, a weft diameter of 0.14 mm to 0.2 mm, a pore size of 60-100 mesh, and a thickness of 1.2 mm to 3.4 mm. This allows the first surface of the mold to better form the protruding and recessed structures, thereby effectively increasing the fit and contact surface area of ​​the biorepair membrane after freeze-drying.

[0140] In some specific embodiments of the present invention, the stainless steel wire used to braid the first layer has a warp diameter of 0.25 mm and a weft diameter of 0.18 mm. The aperture of the first layer is 80 meshes, and the thickness of the first layer is 2 mm.

[0141] In some embodiments of the present invention, the diameter of the stainless steel wire used to braid the second layer is 0.04 mm to 0.045 mm, the pore size of the second layer is 250-300 mesh, and the thickness of the second layer is 0.3 mm to 0.7 mm. This results in the second surface of the second layer being relatively flat and having dense and small pores.

[0142] In some embodiments of the present invention, the pore size of the second layer is 0.0446 mm to 0.0556 mm.

[0143] In some specific embodiments of the present invention, the second layer of the mold is made of plain-weave stainless steel wire with a diameter of 0.042 mm, a pore size of 0.05 mm, and a thickness of 0.5 mm. The use of finer stainless steel wire results in densely packed, finely woven pores and a smooth surface on the second surface of the mold, enabling the bioremediation membrane material to be pressed into a relatively flat morphology.

[0144] In some embodiments of the present invention, the raised and recessed structures are arranged alternately, with the spacing between adjacent raised structures in the longitudinal direction ranging from 0.14 mm to 0.2 mm, and the spacing between adjacent raised structures in the latitudinal direction ranging from 0.2 mm to 0.28 mm. This allows the biorepair membrane formed with these raised and recessed structures to adhere tightly to the tissue defect, blocking the ingress of external soft tissue cells and isolating soft tissue from growing into the bone defect, achieving a good therapeutic effect.

[0145] In some specific embodiments of the present invention, the protruding structures and the recessed structures are arranged alternately, and the spacing between adjacent protruding structures in the longitudinal direction is 0.15 mm, and the spacing between adjacent protruding structures in the weft direction is 0.26 mm.

[0146] In some embodiments of the present invention, the weft wire diameter of the stainless steel wire used to weave the first layer is a first wire diameter, and the warp wire diameter of the stainless steel wire used to weave the first layer is a second wire diameter. The raised structures and the recessed structures are alternately arranged, and the spacing between adjacent raised structures in the warp direction is equal to the first wire diameter, and the spacing between adjacent raised structures in the weft direction is equal to the second wire diameter.

[0147] In some embodiments of the present invention, the warp diameter of the stainless steel wire used to braid the first layer is the second wire diameter, the protruding structures and the recessed structures are alternately arranged, and the height difference between the protruding structures and the recessed structures is equal to the second wire diameter.

[0148] In some embodiments of the present invention, the protruding structures and the concave structures are arranged alternately, and the height difference between the protruding structures and the concave structures is 0.2 mm to 0.28 mm.

[0149] In some embodiments of the present invention, the mold has a length of 6 to 10 centimeters, a width of 4 to 8 centimeters, and a thickness of 1.5 to 4.1 millimeters. The mold is lightweight and does not damage the bioremediation membrane during preparation. While maintaining a good pressing effect, it also saves material and reduces investment costs.

[0150] In some specific embodiments of the present invention, the mold is a thin plate structure of 8 cm × 6 cm, which can meet the size required for the existing biorepair membrane pressing and freeze-drying process, will not cause the biorepair membrane material to be deformed by compression, and also saves freeze-drying mold production materials.

[0151] In some embodiments of the present invention, the first and second layers are welded together using micro-spot resistance welding or seamless butt welding. This results in a mold with no protruding welds or burrs, and the first and second layers are tightly bonded without gaps, preventing delamination or shedding, and exhibiting high stability.

[0152] In some embodiments of the present invention, the first and second layers each include 4 to 8 layers of stainless steel mesh. Excessive layers may result in poor air permeability and permeability, which may affect the freeze-drying effect of the bioremediation membrane. Excessive layers may result in a light overall weight, which may affect the mold's ability to compress the bioremediation membrane.

[0153] In some specific embodiments of the present invention, the steps of preparing the mold include:

[0154] Step 1: The mold uses 316L stainless steel wire to weave two stainless steel wire meshes with different structures in a dense weave method and a twill weave method, and five of each are made;

[0155] Step 2: Laminating and pressing five stainless steel wire meshes woven in a dense weave manner so that their surfaces are flush, and then vacuum sintering them to obtain the first layer; laminating and pressing another five stainless steel wire meshes woven in a twill weave manner so that their surfaces are flush, and then vacuum sintering them to obtain the second layer;

[0156] Step three: seamlessly butt-weld the first layer and the second layer to obtain the mold.

[0157] In some embodiments of the present invention, the surface of the 316L stainless steel wire is electrolytically polished so that it will not rust or deform during use and cleaning.

[0158] In some embodiments of the present invention, the vacuum sintering process is easy to operate, can improve the purity of cemented carbide, and make it have higher pressure resistance and good plasticity, and facilitate subsequent processing, welding and assembly.

[0159] In summary, the present invention utilizes membrane modification technology and methods to maximize the composition and performance characteristics of the composite membrane material to be close to oral soft tissue or bone tissue, thereby improving the biological activity, barrier performance and osteogenesis of the membrane, and making the biorepair membrane have the best repair effect. The present invention combines an allogeneic umbilical cord containing active ingredients with a sodium alginate / chitosan scaffold loaded with hydroxyapatite, and utilizes the mold pressing process of the present invention combined with vacuum freeze drying to prepare a biorepair membrane of umbilical cord and hydroxyapatite composite with multiple effects of biological activity, bone induction, and antibacterial. The biorepair membrane has good biocompatibility, sufficient mechanical strength to maintain a stable space and increase operability, and can induce regeneration of soft tissue.

[0160] While the embodiments of the present invention have been described in detail above, it will be apparent to those skilled in the art that various modifications and variations of these embodiments are possible. However, it should be understood that such modifications and variations are within the scope and spirit of the present invention as set forth in the claims. Furthermore, the invention described herein is susceptible to other embodiments and may be practiced or implemented in a variety of ways.

Claims

1. A bioremediation membrane, characterized in that: include: The gel layer is formed by cross-linking hydroxyapatite, chitosan and sodium alginate, wherein the mass ratio of the chitosan to the sodium alginate is 1:1 to 1:3; An umbilical cord layer is adhered to one side of the gel layer by mold pressing and freeze drying, wherein the umbilical cord layer is a sheet structure composed of umbilical cord tissue, and the umbilical cord tissue is formed from an umbilical cord by mechanically removing vascular cells; When the biorepair membrane is used for oral soft tissue repair, the concentration of hydroxyapatite in the polymer hydrogel matrix composed of chitosan and sodium alginate is 0.1% w / v to 0.3% w / v; When the biorepair membrane is used for bone tissue repair, the concentration of hydroxyapatite in the polymer hydrogel matrix composed of chitosan and sodium alginate is 0.2% w / v to 0.4% w / v.

2. The bioremediation membrane according to claim 1, characterized in that: The side of the umbilical cord layer facing away from the gel layer is a smooth surface, and the side of the gel layer facing away from the umbilical cord layer is an indentation surface, and the indentation surface is provided with a convex structure and a concave structure.

3. The bioremediation membrane according to claim 2, characterized in that: The gel layer and the umbilical cord layer are adhered and fixed by mold pressing and freeze-drying, and the mold includes a first surface and a second surface arranged opposite to each other, the first surface is an indentation surface adapted to the indentation surface, the indentation surface is provided with a convex structure and a concave structure, and the second surface is a smooth surface adapted to the smooth surface.

4. The bioremediation membrane according to claim 1, characterized in that: The umbilical cord tissue originates from human body.

5. The bioremediation membrane according to claim 2, characterized in that: The umbilical cord layer is a double-layer porous structure, comprising a dense layer and a loose layer, the pore size of the dense layer is smaller than that of the loose layer, the loose layer is adhered and fixed to the gel layer, and the dense layer is provided with the smooth surface.

6. The bioremediation membrane according to claim 5, characterized in that: The pore size of the loose layer is 20 μm to 100 μm.

7. A method for preparing a bioremediation membrane, characterized in that: Includes steps: Providing an original umbilical cord, removing blood vessels in the original umbilical cord by mechanical means to form umbilical cord tissue to be shaped, and trimming the umbilical cord tissue to be shaped into an umbilical cord layer with a sheet-like structure; preparing a sodium alginate solution, a chitosan solution and a hydroxyapatite solution respectively, mixing the chitosan solution, the sodium alginate solution and the hydroxyapatite solution uniformly to obtain a gel solution, and then subjecting the gel solution to a cross-linking reaction to obtain a gel layer; The umbilical cord layer is adhered and fixed to the gel layer to prepare the biorepair membrane.

8. The method for preparing a bioremediation membrane according to claim 7, characterized in that: The step of uniformly mixing the chitosan solution, the sodium alginate solution and the hydroxyapatite solution to obtain a gel solution comprises: The chitosan solution is dripped into the sodium alginate solution at a dripping speed of 1 mL / min to 2 mL / min, and stirred to mix uniformly to obtain a polymer hydrogel matrix; The hydroxyapatite solution is added into the polymer hydrogel matrix at a dripping speed of 1 mL / min to 2 mL / min and stirred to mix evenly to obtain the gel solution.

9. The method for preparing a bioremediation membrane according to claim 7, characterized in that: The step of subjecting the gel solution to a cross-linking reaction to obtain a gel layer comprises: Ultrasonic removal of bubbles in the gel solution followed by vacuum freeze drying for 12 h to 24 h to obtain a gel film material; The gel membrane material is soaked in a calcium chloride solution for crosslinking for 0.1 to 1 hour, then soaked in a crosslinker solution for 1 to 4 hours, and then soaked and cleaned with deionized water for 1 to 3 times, and each soaking and cleaning time is 5 to 10 minutes, so as to obtain the gel layer.

10. The method for preparing a bioremediation membrane according to claim 7, characterized in that: The step of adhering and fixing the umbilical cord layer to the gel layer to obtain the biorepair membrane comprises: In an environment with a temperature of 11°C to 15°C, one side of the dense layer in the umbilical cord layer is covered on the smooth surface of the mold, one side of the gel layer is adhered to one side of the loose layer in the umbilical cord layer, and the other indentation surface of the mold is covered on the other side of the gel layer.

11. The method for preparing a bioremediation membrane according to claim 10, characterized in that: The step of adhering and fixing the umbilical cord layer to the gel layer to obtain the biorepair membrane also includes: The mold sandwiched with the umbilical cord layer and the gel layer is allowed to stand at a temperature of -10°C to -22°C for 2h to 6h, and then allowed to stand at a temperature of 0°C to 10°C for 2h to 6h for freeze-thaw treatment. After 1 to 3 freeze-thaw cycles, it is sequentially frozen at -20°C for 2h, -80°C for 4h, -70°C to -80°C for 2h to 14h, and vacuum freeze-dried at -80±5°C for 4h to 8h to obtain the bioremediation membrane.

12. The method for preparing a bioremediation membrane according to claim 7, characterized in that: The step of trimming the umbilical cord tissue to be shaped into an umbilical cord layer with a sheet structure comprises: In an environment with a temperature of 11° C. to 15° C., the umbilical cord tissue to be shaped is cleaned with a cleaning solution, trimmed into sheets and cleaned with deionized water for 1 to 3 times to obtain the umbilical cord layer, and the cleaning temperature is 11° C. to 15° C. and the cleaning time is 15 to 20 minutes.

13. The method for preparing a bioremediation membrane according to claim 9, characterized in that: The cross-linking agent is any one or two of 1-ethyl-(3-dimethylaminopropyl)carbodiimide / N-hydroxysuccinimide, genipin and formaldehyde.

14. The method for preparing a bioremediation membrane according to claim 9, characterized in that: The concentration of the calcium chloride solution is 1% to 5%.

15. The method for preparing a bioremediation membrane according to claim 10, characterized in that: Repeat the steps of covering one side of the dense layer in the umbilical cord layer on the smooth surface of the mold, adhering one side of the gel layer to one side of the loose layer in the umbilical cord layer, and then covering the indentation surface of another mold on the other side of the gel layer, and stacking 2 to 6 layers of the umbilical cord layer and the gel layer in the stacking order of the mold, the umbilical cord layer, the gel layer and another mold to obtain 2 to 6 bioremediation membranes.

16. The method for preparing a bioremediation membrane according to claim 8, characterized in that: The steps of preparing the sodium alginate solution, the chitosan solution and the hydroxyapatite solution respectively include: Weighing sodium alginate, dissolving it in deionized water and stirring it for 1 h to 4 h to prepare the sodium alginate solution; Weigh chitosan and dissolve it in a dilute acid solution with a concentration of 1 wt% to 2 wt% and stir for 1 h to 4 h to prepare the chitosan solution; Weigh hydroxyapatite and place it in deionized water, and mix it evenly by ultrasonic treatment for 0.5 h to 2 h to prepare the hydroxyapatite solution.

17. The method for preparing a bioremediation membrane according to claim 12, characterized in that: The cleaning solution is any one or more of sterile phosphate buffer solution, sterile sodium chloride injection and purified water.

Citation Information

Patent Citations

  • Preparation method of oral biofilm

    CN104922732A

  • Absorbable oral cavity restoration membrane and preparation method thereof

    CN109513046A

  • Active biological patch and preparation method thereof

    CN111330077A

  • Preparation method of bone repair scaffold

    CN115282335A